Macro stickiness in strategic planning of Malaysia’s higher education - Mhd. Sarif, Suhaimi; Ismail, Yusof (International Islamic University Malaysia, 2013)
Stickiness is an economic phenomenon in terms of cost, imposed preferences, policy paradigm and national priorities that caused planning to be inadequate and less responsive. Purpose of study – This study investigates the influence of macro stickiness in strategic planning of Malaysia’s higher education. Design/methodology/approach – It uses personal interview with academic administrators and representatives of selected academic staff associations to obtain data to accomplish research objectives. Findings – The results show that the informants argued that national unity, economic advantages to attract foreign investment, and sound economic growth influenced the strategic planning of Malaysia’s higher education. Research limitations and/or implications –The results of the study are essential to assist policy makers and strategic planners in formulating Malaysia’s higher education policy. Originality/value – Recent study on “macro” level stickiness confirms that policy makers and government confirmed that the government cannot exclude previous policy documents that contained three major elements, i.e., national unity, foreign direct investment and sound economic growth in designing national economic and social policies.